Groundwater analysis for unconfined and clayey layer by using response surface methodology - Musa, Sabariah; Ng, Le Bin; Abduh Algheethi, Adel Ali Saeed; Zakaria, Nor Azazi; Lau, Tze Liang (Penerbit Akademia Baru, 2020)
Groundwater as a source of water stored in aquifers plays an important role in domestic use. However, excessive and uncontrolled water pump activities have side effects such as soil deposition and groundwater reduction. Therefore, Response Surface Methodology (RSM) is an alternative method to optimize the time and quantity of groundwater pumps based on other wells water level changes. The analysis using Design Expert version 10 involves changing the water level at the main wells R1 and R5 with the monitoring of other wells at R2, R3, and R4 within 245 minutes with 48 samples. Based on 4 hours of pump test in different wells, it shows that groundwater production rates indirectly affect pump power factor, water level change, wells location, pump time, and infiltration of soil. R1 (1 hp) has a groundwater rate of 28.65 m3/day, while R5 (2 hp) with 103.63 m3/day. The selection of ANOVA Design-Expert model suitable for R1.R2, R3, R4 and R5 has been evaluated and shows that optimum time is 116.24 minutes (1 hour 55 minutes) for case 1 and 117.48 minutes (1-hour 57 minute) for case 2. In conclusion, this study provides best and suitable pumping time towards the water balance of groundwater. Hence, the reaction from environment and the influences of other factors play an important role in ensuring the continuous water supplement of groundwater.